2007
DOI: 10.1021/jm0611152
|View full text |Cite
|
Sign up to set email alerts
|

Structure−Selectivity Investigations of D2-Like Receptor Ligands by CoMFA and CoMSIA Guiding the Discovery of D3Selective PET Radioligands

Abstract: Elucidation of the physiological role of the D3 receptor and its distribution in the brain using positron emission tomography (PET) is hampered by the lack of bioavailable subtype selective tracer ligands. To develop appropriate D3 radioligands, we designed an integrative procedure involving the elucidation of structural features determining D3 selectivity over both congeners D2 and D4 by comparative molecular analysis. Thus, we have successfully generated CoMFA and CoMSIA models based on the affinitiy differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
48
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 48 publications
(51 citation statements)
references
References 67 publications
(109 reference statements)
3
48
0
Order By: Relevance
“…CoMFA and CoMSIA: Taking advantage of our recently described 3D-QSAR models, [31,32] the prediction of D3 selectivities over both congeners D2 and D4 was a crucial part of our strategy. Based on the affinity differences of a training set of 79 ligands, the putative selectivities of the test compounds 4 a-d were calculated.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…CoMFA and CoMSIA: Taking advantage of our recently described 3D-QSAR models, [31,32] the prediction of D3 selectivities over both congeners D2 and D4 was a crucial part of our strategy. Based on the affinity differences of a training set of 79 ligands, the putative selectivities of the test compounds 4 a-d were calculated.…”
Section: Resultsmentioning
confidence: 99%
“…The predicted selectivities of the test compounds 4 a-d suggested a subtype-selective profile that is further improved or at least comparable with that of previously investigated fluoro-substituted aryl carboxamides. [30,32] According to these encouraging data, the synthesis of the calculated ligands was envisioned.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on our work on SAR studies guiding the development of D3-selective lead compounds, [3,34,35] we recently reported . [35] In the present work we extended this series of compounds and evaluated the D3 binding specificity of their 18 F-labelled versions in vivo.…”
Section: Introductionmentioning
confidence: 99%
“…[35] In the present work we extended this series of compounds and evaluated the D3 binding specificity of their 18 F-labelled versions in vivo. We describe the influence of structural changes on a focused library of fluorinated pyridinylbenzamides that were predicted for adequate D3 selectivities and affinities by using CoMFA and CoMSIA methods.…”
Section: Introductionmentioning
confidence: 99%